Comparative Histopathological Changes Between Primary Versus Recurrent Rhinosinusitis with Nasal Polyposis - Wael Fawzy Ismaiel (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Chronic rhinosinusitis associated with nasal polypi [CRSwNP] is one of the two major chronic rhinosinusitis phenotypes. The histopathological changes of such condition may differ between primary and chronic types.Aim of the work: To differentiate between primary and chronic rhinosinusitis with polypi through detection of the histopathological changes of nasal mucosa.Patients and Methods: Eighty-five patients with CRSwNP scheduled for functional endoscopic sinus surgery (FESS) were divided into two groups; group (1) 35 patients with primary polyposis, group (2) 50 patients with chronic polyposis. A swab was taken from sinus mucosa during FESS and sent for histopathological investigation.Results: We studied 12 histopathogical findings of spacemen of sinus mucosa and found 7 of them had a significant value in comparison between primary and recurrent CRSwNP. The significant increases in chronic recurrent group (2) than primary group (1) were eosinophilic cell count (p=0.044), eosinophilic cell aggregation (p=0.049), basement membrane thickness (P=0.021), Mucosal ulceration (p=0.002), hyperplastic or papillary change (p=0.029), fibrosis (p=0.002) and fungal element (p=0.003).Conclusion: Histopathological findings of sinus mucosa during FESS operation found to be of great value in differentiating between primary and recurrent CRSwNP, however, further studies on large scale groups were recommended to confirm these results.